Utilization of PowerPoint Multimedia Application in Thesis Defense Presentations by Undergraduate Students of the Japanese Language Education Program at Universitas Riau - Harahap, Kaina Sherin Dwi Amelia; Arza Aibonotika; Intan Suri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe the utilization of multimedia in PowerPoint presentations during thesis defense by students of the Japanese Language Education Program, Faculty of Teacher Training and Education, Universitas Riau for the academic year 2024/2025, based on Richard E. Mayer's cognitive multimedia theory. The research employs a qualitative descriptive method with data consisting of ten PowerPoint presentation files from students, which were analyzed using the principles of cognitive multimedia, namely the multimedia, coherence, modality, contiguity, redundancy, personalization, temporal contiguity, signaling, and segmenting principles. The results show that the majority of students have not fully applied these principles optimally. Presentations are predominantly dominated by the use of a single channel (text), excessive information, and irrelevant elements. Only a small portion of the presentations show the utilization of multimedia in accordance with Mayer’s theory. These findings indicate the need for increased student understanding of the basic concepts of multimedia learning so that the information conveyed in academic presentations is more effective, engaging, and easier to understand.